A comprehensive insight of innovations and recent advancements in nanocarriers for nose-to-brain drug targeting - Naeem Mubarak; Muhammad Ahsan Waqar; Asad Majeed Khan; Zainab Asif; Aima Subia Alvi; Aqsa Arshad Virk; Sakeena Amir (Designed Monomers and Polymers)
Central Nervous System (CNS) disorders are the leading cause of illness and affect the everyday lives of people all around the globe and are predicted to increase tremendously in the upcoming decades. Traditional methods of delivering drugs to the CNS face considerable limitations. Nose-to-brain targeting offers a promising alternative that bypasses the blood-brain barrier (BBB), enabling targeted drug administration to the central nervous system (CNS). Nanotechnology has brought forward innovative solutions to the challenges of drug delivery in CNS disorders. Nanocarriers such as liposomes, nanoparticles, nanoemulsions and dendrimers can enhance drug stability, bioavailability, and targeted delivery to the brain. These nanocarriers are designed to overcome physiological barriers and provide controlled and sustained drug release directly to the CNS. Nanocarrier technology has made significant strides in recent years, enabling more effective and targeted delivery of drugs to the brain. With recent advancements, intranasal delivery coupled with nanocarriers seems to be a promising combination that can provide better clinical profiles, pharmacokinetics, and pharmacodynamics for neurodegenerative disorders. This study focuses on exploring the nose-to-brain drug delivery system, emphasizing the use of various nanocarriers designed for this purpose. Additionally, the study encompasses recent advancements in nanocarrier technology tailored specifically to improve the efficiency of drug administration through the nasal route to the brain.